The effect of imipenem and diffusible signaling factors on the secretion of outer membrane vesicles and associated Ax21 proteins in Stenotrophomonas maltophilia - Devos, Simon; Van Oudenhove, Laurence; Stremersch, Stephan; Van Putte, Wouter; De Rycke, Riet; Van Driessche, Gonzalez; Vitse, Jolien; Raemdonck, Koen; Devreese, Bart (Frontiers in Microbiology, 2015)
Outer membrane vesicles (OMVs) are small nanoscale structures that are secreted by bacteria and that can carry nucleic acids, proteins and small metabolites. They can mediate intracellular communication and play a role in virulence. In this study, we show that treatment with the β-lactam antibiotic imipenem leads to a dramatic increase in the secretion of outer membrane vesicles in the nosocomial pathogen Stenotrophomonas maltophilia. Proteomic analysis of their protein content demonstrated that the OMVs contain the chromosomal encoded L1 metallo-β-lactamase and L2 serine-β-lactamase. Moreover, the secreted OMVs contain large amounts of two Ax21 homologues, i.e. outer membrane proteins known to be involved in virulence and biofilm formation. We show that OMV secretion and the levels of Ax21 in the OMVs are dependent on the quorum sensing diffusible signal system (DSF). More specific, we demonstrate that the S. maltophilia DSF cis-Δ2-11-methyl-dodecenoic acid and, to a lesser extent, the Burkholderia cenocepacia DSF cis-Δ2-dodecenoic acid, stimulate OMV secretion. By a targeted proteomic analysis, we confirmed that DSF-induced OMVs contain large amounts of the Ax21 homologues, but not the β-lactamases. This work illustrates that both quorum sensing and disturbance of the peptidoglycan biosynthesis provoke the release of OMVs and that OMV content is context dependent.